Trends of Indications and Complications of Stoma in a Tertiary Care Hospital - Prabej Alam, Rihan Aslam Khan, Mehwish Ali, Naeem Akhtar Qureshi, Amanullah Bhutto, Ihsanullah Rajar, Zainab Shamim (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To identify the indications and complications of the stoma. Methods: The study covered all patients who attended Outpatients department of General Surgery, Ziauddin Hospital in Karachi and met the inclusion criteria. After describing the study’s process, hazards, and benefits, informed permission was obtained. The patients were followed after 4 weeks in the clinic and assessed for Indications (enteric perforation, intestinal tuberculosis, penetrating injury, intestinal obstruction, blunt abdominal trauma). Complications (excoriation, non-functioning stoma, retraction, prolapsed, stenosis of Stomas, wound infection). The proforma that is supplied at the end was filled out with all the acquired data and utilised electronically for research. Results: The mean age of patients was 38.5 ± 7.4 years and the body mass index was 26.8 ± 6.2 kg/m2. The most common indication for stoma was intestinal tuberculosis (41.0%) followed by enteric perforation (27%). The most common complications of stoma were non-functioning stoma (34.4%) followed by excoriation (23.9%). Stoma indication due to enteric perforation was significantly more common in patients aged between 16 and 40 years (p=0.003). Other indications were not significantly associated with age, BMI, and age. The rate of excoriation was 52 (20.1%) in patients with BMI of more than 24 kg/m2 which is significantly higher as compared to patients with lower BMI (p=0.029). The other complications were not significantly different between the age groups, BMI categories, and gender. Conclusion: The most frequent indications and consequences, respectively, were determined to be non-functioning stomas and intestinal tuberculosis. Reduced stoma development and related problems can be achieved with early detection and treatment of TB and enteric fever. Keywords: Indications, Complications, Stoma, Management, Intestinal Stoma, Ostomy, Colostomy